Morphology Profile and PD-L1 Expression in Non-Small Cell Lung Cancer (NSCLC) Patients - Marliana Nurprilinda; Silphia Novelyn; Sonya Trinur Veronika Siahaan; Frisca Angreni (Indonesian Journal of Global Health Research, 2025)
Lung cancer cases in Indonesia became the second highest with the highest mortality rate in 2022. Various advanced examinations such as histopathology and immunohistochemistry are performed to identify the morphological types of lung cancer. Histopathologically, lung cancer classified into two types are Non-Small Cell Lung Cancer (NSCLC) and Small Cell Lung Cancer (SCLC). After histopathological examination, further immunohistochemical testing is required to help classify the subtype and identify therapeutic markers. One of the markers is the expression of Programmed Death Ligand 1 (PD-L1). Patients with this marker can receive anti-PD-L1 immunotherapy according to the specified criteria. This study determined the morphological profile and PD-L1 expression in patients with Non-Small Cell Lung Cancer (NSCLC) at Siloam MRCCC Semanggi Hospital between 2020 and 2022. The method used was descriptive with a retrospective approach by collecting data from the archives of the Anatomical Pathology Laboratory at Siloam MRCCC Semanggi Hospital. The population in this study comprised all patients diagnosed with NSCLC who underwent PD-L1 IHC testing at Siloam MRCCC Semanggi Hospital between 2020 and 2022. Data collection was conducted using a total sampling method, including all individuals who met the predefined inclusion and exclusion criteria. The final sample consisted of 91 patients diagnosed with NSCLC who had undergone PD-L1 IHC examination during the 2020–2022 period. A total of 91 patients including the inclusion and exclusion criteria were included in the data and analyzed. The analysis revealed that the age group 60-69 years accounted for 39.5% of cases, 54.9% of cases were male, 73.6% of cases had an adenocarcinoma morphology, and 54.9% of cases had a negative PD-L1. The incidence of NSCLC patients who underwent PD-L1 IHK examination based on age was dominated by the 60-69 year age group, and most of them were male with the most common diagnosis being adenocarcinoma morphology type and PD-L1 expression with negative values.